Early historic timber halls (Area C) (Scottish Historical and Archaeological Internet Reports, 2011)
This chapter focusses on the Anglian hall and an earlier structure upon which it was partly superimposed. Although there is a significant amount of documentary evidence concerning the Northumbrian occupation of south-west Scotland, the archaeological evidence is comparatively sparse so the discovery at Lockerbie is important. Archaeological description is followed by discussion of the phasing and radiocarbon dates. There are specialist reports on fired clay, slag, charred plant remains, animal bone and a residual sherd of Roman pottery.